Preparation method and application of zinc negative electrode with amino-functionalized waste attapulgite coating
By constructing an amino-functional waste concave and concave rock stone coating on the surface of zinc negative electrode, the problems of uneven deposition of Zn2+ and dendrite growth on the surface of zinc negative electrode in zinc ion batteries are solved, and the electrochemical performance and cycle stability of the battery are significantly improved. It is suitable for large-scale Large-scale production.
Patent Information
- Application Number
- CN202411625428.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The problems of dendrites and by-product accumulation caused by the uneven deposition of Zn2+ on the surface of zinc negative electrodes and hydrogen evolution reactions in dendrites and by-product accumulation are limited by their further development.
Using amino functionalized waste concave and concave rock as a protective coating, the hydrophilicity of the electrode is enhanced by grafting the amino functional groups on the aminosilane coupling agent molecule onto the surface of the waste concave and concave rock and coating it on the surface of the zinc negative electrode. and zinc-philicity, guiding uniform deposition of Zn2+.
It effectively inhibits dendrite growth, reduces side reactions, improves the electrochemical performance and cycle stability of the battery, is suitable for large-scale production, and helps the widespread application of zinc ion batteries.
Smart Images

Figure CN119447152A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a preparation method of a zinc negative electrode with an amino-functionalized waste attapulgite coating and application thereof. Background Art
[0002] Since their commercialization in the 1990s, lithium-ion batteries (LIBs) have been used in all aspects of life. However, the uneven distribution and high cost of lithium resources have limited their long-term development, and the safety issues caused by toxic and flammable organic electrolytes have further hindered their large-scale application. Aqueous zinc-ion batteries (ZIBs) use aqueous solutions as electrolytes, which have higher ionic conductivity than organic electrolytes, as well as advantages such as safety, flame retardancy, and low cost. They are considered to be a potential alternative to non-aqueous rechargeable batteries. However, due to the negative surface Zn 2+ The existence of the problem of dendrite growth caused by uneven deposition and the accumulation of byproducts on the electrode surface caused by the hydrogen evolution reaction have hindered the further development of ZIBs.
[0003] In order to improve the stability of the zinc negative electrode, a variety of strategies have been proposed, including the introduction of electrolyte additives, the exploration of new separators, and the development of semi-solid electrolytes. Although these methods have achieved good results, they are usually complicated to operate, costly, and difficult to apply on a large scale. Compared with the above methods, constructing a protective coating on the surface of the zinc negative electrode is a simple and efficient strategy. By constructing an effective artificial solid-electrolyte interface, it can not only guide the uniform electric field distribution, but also promote the Zn 2+ The uniform deposition / stripping of ZnO2 can be achieved, and the layer can be used as a barrier to reduce the corrosion and side reactions of ZnO2. Therefore, it is necessary to find a ZnO2 with high chemical stability, good wettability to electrolyte, and good adhesion to ZnO2. 2+ Artificial solid-electrolyte interface with good affinity to solve the problems of dendrite growth and side reactions of zinc anode. Summary of the invention
[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing a zinc negative electrode with an amino-functionalized waste attapulgite coating and its application, wherein the amino functional groups on the aminosilane coupling agent molecules are grafted onto the surface of the waste attapulgite to obtain the amino-functionalized waste attapulgite, which is then coated on the surface of the zinc negative electrode as a protective coating. The present invention enhances the hydrophilicity of the electrode and guides the uniform deposition of zinc ions, thereby achieving the purpose of inhibiting dendrite growth and reducing the occurrence of side reactions, and greatly improving the electrochemical performance and cycle stability of the battery.
[0005] Technical solution: The present invention provides a method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating, which is characterized by comprising the following steps: S1. placing the purified waste attapulgite in toluene and performing ultrasonication to obtain a waste attapulgite dispersion; S2, mixing the attapulgite dispersion with an aminosilane coupling agent, continuously stirring, washing, filtering, and drying to obtain amino-functionalized waste attapulgite; S3, placing the amino-functionalized waste attapulgite and polyvinylidene fluoride in N-methylpyrrolidone and stirring to obtain slurry; coating the slurry on the surface of zinc foil, and drying to obtain a zinc negative electrode with an amino-functionalized waste attapulgite coating.
[0006] Furthermore, in S1, the purification treatment is specifically as follows: the waste attapulgite and 0.5 mol L-1 hydrochloric acid are mixed and stirred at a mass ratio of 1:10 for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain the purified waste attapulgite.
[0007] Furthermore, in S1, the mass ratio of the waste attapulgite to the toluene is 1:50-200.
[0008] Preferably, in S1, the ultrasonication time is 20-60 min.
[0009] Furthermore, in S2, the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.
[0010] Furthermore, in S2, the mass ratio of the aminosilane coupling agent to the waste attapulgite in the attapulgite dispersion is 1-3:1.
[0011] Preferably, in S2, the specific conditions for the continuous stirring are: stirring temperature is 40-80° C., and stirring time is 6-18 h.
[0012] Preferably, in S2, the drying temperature is 40-80°C.
[0013] Furthermore, in S3, the mass volume ratio of the amino-functionalized waste attapulgite, polyvinylidene fluoride and N-methylpyrrolidone is 9:1:25.
[0014] On the other hand, the present invention provides a use of a zinc negative electrode having an amino-functionalized waste attapulgite coating prepared by any of the methods described above in an aqueous zinc ion battery.
[0015] Furthermore, the aqueous zinc ion battery provided by the present invention is specifically: NH4V4O 10The positive electrode is the zinc foil with amino-functionalized waste attapulgite coating prepared by any of the above methods as the negative electrode, the separator is a glass fiber separator, and the electrolyte is 3 mol L -1 Full battery of Zn(OTF)2 solution; Or, the zinc foil with amino-functionalized waste attapulgite coating prepared by any of the above methods is used as the positive electrode, the zinc foil with amino-functionalized waste attapulgite coating prepared by any of the above methods is used as the negative electrode, the separator is a glass fiber separator, and the electrolyte is 3 mol L -1 Symmetrical battery of Zn(OTF)2 solution.
[0016] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects: The invention obtains amino-functionalized waste attapulgite by grafting the amino functional groups on the aminosilane coupling agent molecules to the surface of waste attapulgite, thereby improving the hydrophilicity and zinc affinity of the waste attapulgite; and then coating the waste attapulgite on the surface of the zinc negative electrode as a protective coating: on the one hand, the introduction of the amino functional groups enhances the hydrophilicity of the waste attapulgite, so that the electrode has better wettability to the electrolyte, thereby accelerating the Zn 2+ On the other hand, zinc ions bind to water molecules in the electrolyte to form a solvated structure with a large ionic radius. When participating in the electrochemical reaction, they undergo a desolvation process. The amino functional groups with good zinc affinity can compete with water molecules for the binding sites of zinc ions, accelerating the transfer of Zn 2+ The desolvation process of Zn 2+ The uniform deposition of Zn can be achieved without dendrites, and the amino-functionalized waste attapulgite coating can act as a barrier to reduce the direct contact between water molecules and the Zn anode, thereby inhibiting the occurrence of corrosion and side reactions.
[0017] The waste attapulgite used in the present invention is widely available and inexpensive, and the synthesis method used is simple, which is helpful for developing negative electrode materials for aqueous zinc ion batteries and zinc ion batteries with stable performance, is suitable for large-scale production, and effectively promotes large-scale application of zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Infrared spectra of the amino-functionalized waste attapulgite (ATP-NH2) material and the waste attapulgite (ATP) material prepared in Embodiment 1; Figure 2 The contact angle measurement results of the zinc foil coated with the functionalized waste attapulgite coating and the original zinc foil prepared in Embodiment 1; Figure 3 The symmetric zinc ion battery comprising the functionalized waste attapulgite-coated zinc foil in embodiment 1 and the symmetric zinc ion battery comprising the original zinc foil at a current density of 1 mA cm -2 Cycle performance diagram of Figure 4 The zinc ion full battery containing the functionalized waste attapulgite-coated zinc foil in embodiment 1 and the zinc ion full battery containing the original zinc foil at 2 A g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0018] The present invention is described in further detail below.
[0019] Implementation 1: A method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating comprises the following steps: Waste attapulgite and 0.5 mol L-1 hydrochloric acid were mixed and stirred at a mass ratio of 1:10 for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain purified waste attapulgite. 0.5 g of purified waste attapulgite was added to 100 g of toluene, and the waste attapulgite dispersion was obtained after ultrasonic treatment for 20 min. The dispersion was then transferred to a round-bottom flask, 0.5 g of APTMS was added, and the mixture was stirred at 40 °C for 18 h. After the reaction, the product was washed with toluene and ethanol, filtered, and dried at 40 °C to obtain amino-grafted functionalized waste attapulgite.
[0020] 90 mg of functionalized waste attapulgite and 10 mg of polyvinylidene fluoride were added to 250 mg of N-methylpyrrolidone and stirred to obtain a slurry, which was coated on the surface of zinc foil with a coating machine and then vacuum dried to obtain a zinc negative electrode (Zn@ATP-NH2) with an amino-functionalized waste attapulgite coating.
[0021] Using NH4V4O 10 Or Zn@ATP-NH2 as the positive electrode, Zn@ATP-NH2 as the negative electrode, glass fiber as the separator, and 3 mol / L Zn(OTF)2 solution as the electrolyte to assemble a 2025 type button zinc ion battery.
[0022] The assembled battery was subjected to electrochemical performance testing. The symmetrical battery 2 The test was carried out under a current density of , and the schematic diagram of the symmetrical battery cycle performance is shown in Figure 3 As shown; the full battery was tested at a current density of 2 A / g, and the cycle performance diagram is shown in Figure 4 shown.
[0023] Implementation 2: A method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating comprises the following steps: Waste attapulgite and 0.5 mol L-1 hydrochloric acid were mixed and stirred at a mass ratio of 1:10 for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain purified waste attapulgite. 0.5 g of purified waste attapulgite was added to 80 g of toluene, and the waste attapulgite dispersion was obtained after ultrasonic treatment for 35 min. The dispersion was then transferred to a round-bottom flask, 1.2 g of APTES was added, and the mixture was stirred at 50 °C for 12 h. After the reaction, the product was washed with toluene and ethanol, filtered, and dried at 50 °C to obtain amino-grafted functionalized waste attapulgite.
[0024] 90 mg of functionalized waste attapulgite and 10 mg of polyvinylidene fluoride were added to 250 mg of N-methylpyrrolidone and stirred to obtain a slurry, which was coated on the surface of zinc foil with a coating machine and then vacuum dried to obtain a zinc negative electrode (Zn@ATP-NH2-2) with an amino-functionalized waste attapulgite coating.
[0025] Using NH4V4O 10 Or Zn@ATP-NH2-2 as the positive electrode, Zn@ATP-NH2-2 as the negative electrode, glass fiber as the separator, and 3 mol / L Zn(OTF)2 solution as the electrolyte to assemble a 2025 type button zinc ion battery.
[0026] The assembled battery was subjected to electrochemical performance testing. The symmetrical battery 2 The full battery was tested at a current density of 2 A / g. The test results of the cycle performance of the full battery are listed in Table 2.
[0027] Implementation 3: A method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating comprises the following steps: Waste attapulgite and 0.5 mol L-1 hydrochloric acid were mixed and stirred at a mass ratio of 1:10 for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain purified waste attapulgite. 0.8 g of purified waste attapulgite was added to 80 g of toluene, and the waste attapulgite dispersion was obtained after ultrasonic treatment for 40 min. The dispersion was then transferred to a round-bottom flask, 2 g of AEAPMS was added, and the mixture was stirred at 60 °C for 10 h. After the reaction, the product was washed with toluene and ethanol, filtered, and dried at 60 °C to obtain amino-grafted functionalized waste attapulgite.
[0028] 90 mg of functionalized waste attapulgite and 10 mg of polyvinylidene fluoride were added to 250 mg of N-methylpyrrolidone and stirred to obtain a slurry, which was coated on the surface of zinc foil with a coating machine and then vacuum dried to obtain a zinc negative electrode (Zn@ATP-NH2-3) with an amino-functionalized waste attapulgite coating.
[0029] Using NH4V4O 10 Or Zn@ATP-NH2-3 as the positive electrode, Zn@ATP-NH2-3 as the negative electrode, glass fiber as the separator, and 3 mol / L Zn(OTF)2 solution as the electrolyte to assemble a 2025 type button zinc ion battery.
[0030] The assembled battery was subjected to electrochemical performance testing. The symmetrical battery 2 The full battery was tested at a current density of 2 A / g. The test results of the cycle performance of the full battery are listed in Table 2.
[0031] Implementation 4: A method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating comprises the following steps: Waste attapulgite and 0.5 mol L-1 hydrochloric acid were mixed and stirred at a mass ratio of 1:10 for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain purified waste attapulgite. 1 g of purified waste attapulgite was added to 50 g of toluene, and the waste attapulgite dispersion was obtained after ultrasonic treatment for 60 min. The dispersion was then transferred to a round-bottom flask, 3 g of AEAPTES was added, and the mixture was stirred at 80 °C for 6 h. After the reaction, the product was washed with toluene and ethanol, filtered, and dried at 80 °C to obtain amino-grafted functionalized waste attapulgite.
[0032] 90 mg of functionalized waste attapulgite and 10 mg of polyvinylidene fluoride were added to 250 mg of N-methylpyrrolidone and stirred to obtain a slurry, which was coated on the surface of zinc foil with a coating machine and then vacuum dried to obtain a zinc negative electrode (Zn@ATP-NH2-4) with an amino-functionalized waste attapulgite coating.
[0033] Using NH4V4O 10 Or Zn@ATP-NH2-4 as the positive electrode, Zn@ATP-NH2-4 as the negative electrode, glass fiber as the separator, and 3 mol / L Zn(OTF)2 solution as the electrolyte to assemble a 2025 type button zinc ion battery.
[0034] The assembled battery was subjected to electrochemical performance testing. The symmetrical battery 2The full battery was tested at a current density of 2 A / g. The cycle performance test results of the full battery are listed in Table 2.
[0035] Comparative Example 1: This comparative example is substantially the same as the embodiment 1, except that the amount of APTMS added in this comparative example is 0.1 g. The assembled battery is tested under the same test conditions, and the test results of the full battery cycle performance are listed in Table 1.
[0036] Apart from this, this comparative example is completely the same as Implementation Example 1 and will not be described in detail here.
[0037] Comparative Example 2: This comparative example is substantially the same as Embodiment 2, except that the amount of toluene used in this comparative example is 150 g. The assembled battery is tested under the same test conditions, and the test results of the full battery cycle performance are listed in Table 1.
[0038] Apart from this, this comparative example is exactly the same as Implementation Example 2 and will not be described in detail here.
[0039] Comparative Example 3: This comparative example is substantially the same as Embodiment 2, except that the ultrasonic time in this comparative example is 10 min. The assembled battery is tested under the same test conditions, and the test results of the full battery cycle performance are listed in Table 1.
[0040] Comparative Example 4: This comparative example is substantially the same as the embodiment 2, except that the stirring temperature in this comparative example is 25° C. The assembled battery is tested under the same test conditions, and the test results of the full battery cycle performance are listed in Table 1.
[0041]
[0042] Result analysis: from Figure 1 It can be seen from the infrared spectra of the amino-functionalized waste attapulgite material and the waste attapulgite material obtained in Implementation Example 1 that the characteristic band of ATP is located at 1200-930 cm -1 , located at 3617 and 3546 cm -1 The absorption peak at 2930 cm is due to the stretching vibration of -OH on the surface of waste attapulgite. -1 The absorption bands at 2520 and 1800 cm correspond to the CH stretching vibration of the -CH2 group on the APTMS molecule, which indicates that the APTMS molecule is grafted onto ATP. -1 The appearance of a new band further demonstrates the successful introduction of the -NH2 functional group.
[0043] from Figure 2 The contact angle measurement results of the zinc foil coated with the amino-functionalized waste attapulgite coating and the original zinc foil prepared in Implementation Example 1 show that the modified Zn@ATP-NH2 has a smaller contact angle than the original zinc foil, indicating that the coating of the amino-functionalized waste attapulgite enhances the hydrophilicity of the electrode surface, which is beneficial to improve the wettability of the electrode, and provides a reference for the research on the contact angle of Zn@ATP-NH2. 2+ Transport establishes a fast transfer channel to promote Zn 2+ Rapid and uniform deposition.
[0044] from Figure 3 The symmetric zinc ion battery containing the amino-functionalized spent attapulgite-coated zinc foil in embodiment 1 and the symmetric zinc ion battery containing the original zinc foil at a current density of 1 mA cm -2 As can be seen in the cycling performance diagram below, the symmetric battery using the original zinc foil short-circuited and failed after 94 h, which was caused by dendrites piercing the separator. The symmetric battery using Zn@ATP-NH2 remained stable after 1000 h of cycling, indicating that the coating modification of amino-functionalized waste attapulgite can effectively inhibit the generation of zinc dendrites and improve the cycling stability of the zinc negative electrode.
[0045] from Figure 4 The Zn-ion full battery containing the functionalized waste attapulgite-coated zinc foil in Embodiment 1 and the Zn-ion full battery containing the original zinc foil at 2 A g -1 The cycling performance diagram under current density shows that the first discharge capacity of the full battery using the original zinc foil is 247.92 mAh g -1 , and failed after short circuit after 667 cycles. The first discharge capacity of the full battery using the Zn@ATP-NH2 negative electrode is 262.49 mAh g -1 After 1000 cycles, it still retains 174.78 mAh g -1 The specific capacity of the battery is 66.58%, and the capacity retention rate is 66.58%. This shows that the full battery using the Zn@ATP-NH2 negative electrode has better cycle stability. This is because the presence of the amino-functionalized waste attapulgite coating enhances the wettability of the electrode surface, guiding the Zn 2+ Uniform deposition. And -NH2 functional group has good 2+ Better affinity can promote Zn 2+ The desolvation process reduces the corrosion of free water molecules on the zinc negative electrode, thereby improving the cycle stability of the battery.
[0046] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating, characterized in that: The following steps are involved: S1. placing the purified waste attapulgite in toluene and performing ultrasonication to obtain a waste attapulgite dispersion; S2, mixing the attapulgite dispersion with an aminosilane coupling agent, continuously stirring, washing, filtering, and drying to obtain amino-functionalized waste attapulgite; S3, placing the amino-functionalized waste attapulgite and polyvinylidene fluoride in N-methylpyrrolidone and stirring to obtain slurry; coating the slurry on the surface of zinc foil, and drying to obtain a zinc negative electrode with an amino-functionalized waste attapulgite coating.
2. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S1, the purification treatment is specifically as follows: waste attapulgite and 0.5 mol L -1 The mixture was mixed with hydrochloric acid in a mass ratio of 1:10 and stirred for 24 h, then centrifuged and washed with deionized water until neutral, and finally freeze-dried to obtain the purified waste attapulgite.
3. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S1, the mass ratio of the waste attapulgite to the toluene is 1:50-200.
4. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S1, the ultrasonication time is 20-60 min.
5. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S2, the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.
6. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S2, the mass ratio of the aminosilane coupling agent to the waste attapulgite in the attapulgite dispersion is 1-3:
1.
7. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S2, the specific conditions for the continuous stirring are: stirring temperature is 40-80° C., and stirring time is 6-18 h.
8. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S2, the drying temperature is 40-80°C.
9. The method for preparing a zinc negative electrode having an amino-functionalized waste attapulgite coating according to claim 1, characterized in that: In S3, the mass volume ratio of the amino-functionalized waste attapulgite, polyvinylidene fluoride and N-methylpyrrolidone is 9:1:
25.
10. Use of a zinc negative electrode having an amino-functionalized waste attapulgite coating prepared by the method according to any one of claims 1 to 9 in an aqueous zinc ion battery.